2022
DOI: 10.1002/adfm.202205723
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and CNT‐Based Smart Fiber‐Reinforced Composites: A Review

Abstract: Multifunctional fiber-reinforced polymer (FRP) composites provide an ideal platform for next-generation smart composites applications including structural health monitoring, electrical and thermal conductivity, energy storage and harvesting, and electromagnetic interference shielding without compromising their mechanical properties. Recent progress in carbon-based nanomaterials such as graphene and carbon nanotubes (CNTs) has enabled the development of many novel multifunctional composites with excellent mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 322 publications
0
50
0
1
Order By: Relevance
“…The type, length, arrangements, and orientation of fibers define the properties and structural behavior of the final composites. [ 35 ]…”
Section: Fiber Reinforced Polymer (Frp) Composites and Manufacturing ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The type, length, arrangements, and orientation of fibers define the properties and structural behavior of the final composites. [ 35 ]…”
Section: Fiber Reinforced Polymer (Frp) Composites and Manufacturing ...mentioning
confidence: 99%
“…[ 212 ] Several carbonaceous materials were reported to be utilized for the modification of natural fiber reinforced composites, in particular carbon nanotubes (CNTs). [ 35 ] Shen et al [ 213 ] treated ramie fibers/epoxy composites with different CNT contents ranging from 0 to 0.6 wt.% and the investigation showed that, interlaminar shear strength (ILSS), flexural strength, and flexural modulus were improved by about 38%, 34%, and 37% respectively. Islam et al, [ 214 ] increased the mechanical strength of jute fibers composites by dip‐drying jute fibers with CNTs.…”
Section: Modifications For Sustainable Frp Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the similarity of functions, the epidermis layer of skin provides a barrier for the substrate, and the dermis layer confers good exibility and elasticity to the skin, providing insulation, buffering external shock and self-healing function of skin tissue damage [28]. Similarly, the polyurethane layer composed of exible molecular chains containing dynamic hydrogen and disul de bonds provides exibility, elasticity and self-healing functions to the coating, while the CNTs layer is relatively rigid and dense, which endows the polyurethane elastomer layer with a signi cant barrier effect and mechanical strength [29]. Figure 1b shows that the SFPUHE-HTF-CNTs have a distinct layered structure, with the inner layer composed of self-healing polyurethane and the outer layer composed of CNTs.…”
Section: Fabrication and Structural Characterization Of Sfpuhe-htf An...mentioning
confidence: 99%
“…[25] Among them, graphene, a single atom thick 2D closely packed honeycomb lattice of sp 2 carbon allotropes, has received much attention from the researcher community, owing to its excellent mechanical, thermal, electrical, and other properties. [26][27][28] Since its isolation in 2004, graphene and graphene-like 2D materials have shown great promise as transduction system and supporting substrates for fabricating next generation electronics, especially biosensors. Their extremely high surface area, coupled with a broad range of electrical and optical properties, makes them ideal for biosensing applications.…”
Section: Introductionmentioning
confidence: 99%